Introduction to pharmaceutical analytical chemistry - Pedersen-Bjergaard, Stig; Pedersen-Bjergaard, Stig; Gammelgaard, Bente; Halvorsen, Trine G. (Trine Grønhaug), 1975- (Hoboken, NJ : Wiley, 2019)
"The definitive textbook on the chemical analysis of pharmaceutical drugs;- fully revised and updated Introduction to Pharmaceutical Analytical Chemistry enables students to gain fundamental knowledge of the vital concepts, techniques and applications of the chemical analysis of pharmaceutical ingredients, final pharmaceutical products and drug substances in biological fluids. A unique emphasis on pharmaceutical laboratory practices, such as sample preparation and separation techniques, provides an efficient and practical educational framework for undergraduate studies in areas such as pharmaceutical sciences, analytical chemistry and forensic analysis. Suitable for foundational courses, this essential undergraduate text introduces the common analytical methods used in quantitative and qualitative chemical analysis of pharmaceuticals. This extensively revised second edition includes a new chapter on chemical analysis of biopharmaceuticals, which includes discussions on identification, purity testing and assay of peptide and protein-based formulations. Also new to this edition are improved full-colour illustrations and tables, a streamlined chapter structure and text revised for increased clarity and comprehension. Introduces the fundamental concepts of pharmaceutical analytical chemistry and statistics Presents a systematic investigation of pharmaceutical applications absent from other textbooks on the subject Examines various analytical techniques commonly used in pharmaceutical laboratories Provides practice problems, up-to-date practical examples and detailed illustrations Includes updated content aligned with the current European and United States Pharmacopeia regulations and guidelines Covering the analytical techniques and concepts necessary for pharmaceutical analytical chemistry, Introduction to Pharmaceutical Analytical Chemistry is ideally suited for students of chemical and pharmaceutical sciences as well as analytical chemists transitioning into the field of pharmaceutical analytical chemistry"--
"This textbook is an extensive revision of "Introduction to Pharmaceutical Analysis" from 2012. We have revised the manuscript totally, and updated the content according to current practice of pharmaceutical analytical chemistry, and according to current versions of European Pharmacopoeia and United States Pharmacopeia. Also, we have added a new chapter on chemical analysis of biopharmaceuticals, and illustrations have been improved and are now in colour. The intention of these efforts has been to provide the reader with a textbook at the level expected in year 2018"--
Revision of: Introduction to pharmaceutical chemical analysis / Steen Hansen, Stig Pedersen-Bjergaard, Knut Rasmussen. 2012.
Includes bibliographical references and index.
Keywords: Drugs -- Analysis; Pharmaceutical chemistry; SCIENCE / Chemistry / Analytic